Buckling behaviour of S960 ultra-high strength steel welded I-section columns - Tee, Victory Wei Liang (Nanyang Technological University, 2020)
This paper shows a comprehensive experimental and numerical modelling programme on the material properties and buckling behaviour of welded I-sections columns fabricated from grade S960 ultra-high-strength steel plates. Tests including material tensile coupon tests, residual stress measurements, initial local geometric imperfection measurements, sixteen stud column tests and ten long column tests were performed on ten GMA (gas metal arc) welded I-sections columns. Numerical modelled I-sections columns were then developed and validated against the experimental results. The suitability of the slenderness limits and buckling resistances from the design provisions listed in Eurocode, AISC and Australian Standard for ultra-high-strength welded I-section columns were then evaluated based on the obtained experimental and numerical data. The comparisons generally showed that the established slenderness limits are applicable for the welded UHSS S960 I-sections columns, and the given cross-section buckling resistances in these codes are providing a conservative prediction for S960 UHSS welded I-sections columns.